Altered in vitro muscle differentiation in X-linked myopathy with excessive autophagy - Stephanie A. Fernandes; Camila F. Almeida; Lucas S. Souza; Monize Lazar; Paula Onofre-Oliveira; Guilherme L. Yamamoto; Letícia Nogueira; Letícia Y. Tasaki; Rafaela R. Cardoso; Rita C. M. Pavanello; Helga C. A. Silva; Merari F. R. Ferrari; et al. (The Company of Biologists, 2020)
X-linked myopathy with excessive autophagy (XMEA) is a genetic disease associated with weakness of the proximal muscles. It is caused by mutations in the VMA21 gene, coding for a chaperone that functions in the vacuolar ATPase (v-ATPase) assembly. Mutations associated with lower content of assembled v-ATPases lead to an increase in lysosomal pH, culminating in partial blockage of macroautophagy, with accumulation of vacuoles of undigested content. Here, we studied a 5-year-old boy affected by XMEA, caused by a small indel in the VMA21 gene. Detection of sarcoplasmic Lc3 (also known as MAP1LC3B)-positive vacuoles in his muscle biopsy confirmed an autophagy defect. To understand how autophagy is regulated in XMEA myogenesis, we used patient-derived muscle cells to evaluate autophagy during in vitro muscle differentiation. An increase in lysosomal pH was observed in the patient's cells, compatible with predicted functional defect of his mutation. Additionally, there was an increase in autophagic flux in XMEA myotubes. Interestingly, we observed that differentiation of XMEA myoblasts was altered, with increased myotube formation observed through a higher fusion index, which was not dependent on lysosomal acidification. Moreover, no variation in the expression of myogenic factors nor the presence of regenerating fibers in the patient's muscle were observed. Myoblast fusion is a tightly regulated process; therefore, the uncontrolled fusion of XMEA myoblasts might generate cells that are not as functional as normal muscle cells. Our data provide new evidence on the reason for predominant muscle involvement in the context of the XMEA phenotype. This article has an associated First Person interview with the first author of the paper.